Rational competent electrocatalytic oxygen evolution reaction on stable tailored ternary MoO3‐NiO‐activated carbon hybrid catalyst. (26th April 2022) - Patil, Komal N.; Shinde, Pratik V.; Srinivasappa, Puneethkumar M.; Nabgan, Walid; Chaudhari, Nitin K.; Rout, Chandra Sekhar; Jadhav, Arvind H.
Summary: Rational designing of advanced electrocatalysts for oxygen evolution reaction (OER) for energy sustainability is challenging. In this perspective, the fabrication of an efficient ternary hybrid composite electrocatalyst consisting of carbon‐based materials and earth‐abundant metal oxides can be thought as a better choice for large‐scale applications. Hybrid of MoO3 and NiO with carbon material would possibly improve stability and conductivity which can assist in improving OER performance. In this regard, we report the development of MoO3 /NiO/activated carbon (MoNiAC) ternary hybrid catalyst by a facile, one‐step solution combustion synthesis (SCS) method. The physiochemical properties of the synthesized catalyst were evaluated by advanced analytical and spectroscopic techniques. The MoNiAC ternary hybrid catalyst exhibited a lower over‐potential (279 mV) (without iR compensation) to attain the current density of 10 mA/cm 2, and small Tafel slope of 89 mV/dec was accompanied. The superior activity could be ascribed to the synergism between MoO3, NiO, and AC. Furthermore, the stability graph of the hybrid demonstrated appreciable durability of catalyst for upto 8.33 h. The characterization of after stability catalyst suggested no major disturbance in the morphology as well as element distribution signifying the high durability of the hybrid catalyst in terms of activity as well as morphology. The remarkable features such as appreciable OER activity, promising kinetics, and robustness ameliorated the performance of MoNiAC hybrid as an electrocatalyst for OER. Abstract : We report the development of MoO3 /NiO/activated carbon (MoNiAC) ternary hybrid catalyst by a facile, one‐step solution combustion synthesis (SCS) method. The MoNiAC ternary hybrid catalyst exhibited a lower over‐potential (279 mV) (without iR compensation) to attain the current density of 10 mA/cm 2, and small Tafel slope of 89 mV/dec was accompanied. Furthermore, the stability graph of the hybrid demonstrated appreciable durability of catalyst for upto 8.33 h.